2022
DOI: 10.2147/idr.s381265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbapenem-Resistant Klebsiella pneumoniae Infection on the Clinical Outcomes of Kidney Transplant Recipients

Abstract: Background: Carbapenem-resistant Klebsiella pneumoniae (CRKP) infection has proven to be difficult to control and typically presents with devastating effects. Methods: This retrospective study was conducted on the renal recipients at our institution between January 2021 to January 2022. Clinical data was collected to identify factors associated with CRKP infection and clinical outcomes. Results: There were 104 cases out of 186 total renal recipients who presented with at least one infection within 3 months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Risk factors for CRE infection have been usually investigated in specific organ transplant settings and most commonly in OLT recipients (see Table 2 ) [ 48 , 75 , 79 , 80 ]. Carriage, either acquired before or after transplant, and peri-surgical complications have been associated with highest risk of developing CRE infection [ 48 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for CRE infection have been usually investigated in specific organ transplant settings and most commonly in OLT recipients (see Table 2 ) [ 48 , 75 , 79 , 80 ]. Carriage, either acquired before or after transplant, and peri-surgical complications have been associated with highest risk of developing CRE infection [ 48 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Usually, CRE infection occurs in the first 4-8 weeks after transplant, earlier infections (within 2 weeks) are observed in pre-transplant carriers and/or in donor derived infections (DDI) [48,53,92]. Notably, incidence of DDI due to CRE is high in China, one study focused on KT patients reported that possible DDI increased the risk of CRE infection by more than six times [75]. Authors reported varying prevalence rates of CRE among donor or preservation fluid cultures, ranging from 1.6% to 19.2% [93][94][95].…”
Section: Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%